Promoting Indonesian university students' critical intercultural awareness in tertiary EAL classrooms: The use of digital photograph-mediated intercultural tasks. (February 2018) - Kusumaningputri, Reni; Widodo, Handoyo Puji
Abstract: Anchored in Byram's (1997) intercultural theory, this article makes a case for critical intercultural awareness, which involves critical understanding, analysis, evaluation, and interpretation of sociocultural realities. Given the importance of intercultural communicative competence (ICC) in English language teaching (ELT), this article reports a classroom-based study investigating the use of digital photograph-mediated intercultural tasks to promote students' critical intercultural awareness in the tertiary ELT context. Sixty six English literature majors volunteered to participate in the study. In this study, data were garnered from students' work artifacts, classroom observations, in-class discussion notes, and field notes. Drawing on qualitative content analysis, findings show that digital photograph-mediated intercultural tasks help the students enhance their critical awareness of cultural realities portrayed in the photographs they navigated online. This study suggests that using both intercultural tasks and digital photographs as culturally-laden learning resources has the potential to promote students' ICC in English language classrooms.